Thomas M. Patterson, The Charter and Ordinances of the City of Denver 78, § 1 (1875) - (:unkn) unknown (My University, 1875)
Prohibited the discharge of any cannon, gun, fowling piece, pistol, fire arms, or fire or explode any squib, cracker, or other thing containing powder or other combustible or explosive material. Violators fined not less than one nor more than one hundred dollars.
Keywords: DISCHARGE